Acceptability of a shared cancer follow‐up model of care between general practitioners and radiation oncologists: A qualitative evaluation - Tiffany Sandell; Heike Schütze; Andrew Miller (Wiley, 2023)
Abstract Introduction Facilitators to implement shared cancer follow‐up care into clinical practice include mechanisms to allow the oncologist to continue overseeing the care of their patient, two‐way information sharing and clear follow‐up protocols for general practitioners (GPs). This paper aimed to evaluate patients, GPs and radiation oncologists (ROs) acceptance of a shared care intervention. Methods Semi‐structured interviews were conducted pre‐ and post intervention with patients that were 3 years post radiotherapy treatment for breast, colorectal or prostate cancer, their RO, and their GP. Inductive and deductive thematical analysis was employed. Results Thirty‐two participants were interviewed (19 patients, 9 GPs, and 4 ROs). Pre intervention, there was support for GPs to play a greater role in cancer follow‐up care, however, patients were concerned about the GPs cancer‐specific skills. Patients, GPs and ROs were concerned about increasing the GPs workload. Post intervention, participants were satisfied that the GPs had specific skills and that the impact on GP workload was comparable to writing a referral. However, GPs expressed concern about remuneration. GPs and ROs felt the model provided patient choice and were suitable for low‐risk, stable patients around 2-3 years post treatment. Patients emphasised that they trusted their RO to advise them on the most appropriate follow‐up model suited to their individual situation. The overall acceptance of shared care depended on successful health technology to connect the GP and RO. There were no differences in patient acceptance between rural, regional, and cancer types. ROs presented differences in acceptance for the different cancer types, with breast cancer strongly supported. Conclusion Patients, GPs and ROs felt this shared cancer follow‐up model of care was acceptable, but only if the RO remained directly involved and the health technology worked. There is a need to review funding and advocate for health technology advances to support integration. Patient or Public Contribution Patients treated with curative radiotherapy for breast, colorectal and prostate cancer, their RO and their GPs were actively involved in this study by giving their consent to be interviewed.